Efektifitas Teknik Counterpressure Untuk Mengurangi Rasa Nyeri Persalinan Kala I Di Praktek Mandiri Bidan Sutra Des Kelissa Kelurahan Bintara Kota Bekasi Periode Juli - Agustus 2022 - Panjaitan, Merry Januarti; Kelissa, Sutra Des (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Labor pain is a physiological process as many as 12%-67% of women feel worried about the pain that will be experienced during labor. Efforts to reduce labor pain are counterpressure techniques. To determine the effectiveness of counterpressure techniques to reduce pain in the first stage of labor in the Independent Practice of the Sutra Midwife Des Kelissa Kel. West Bekasi District Officer in 2022. This study used a quasi-experimental method with a two-Group posttest only design which was divided into two groups. The sampling technique in this study used a total sampling of 30 mothers. Data were collected using observation sheets and analyzed using the Mann Withney U test. The study showed that the counterpressure technique was more effective in reducing the level of pain in active phase maternity mothers as indicated by the p-value equeal to (0.005) less than 0.05, meaning that there was a difference in pain scale between the intervention group and the control group. The counterpressure technique is a good alternative that needs to be recommended to reduce pain intensity in active phase I birth mothers.